APLIKASI KOMPUTASI KIMIA DALAM ANALISIS HUBUNGAN KUANTITATIF STRUKTUR-AKTIVITAS (HKSA) DARI SENYAWA AKTIF ANTIBAKTERI ANALOG N-ALKIL IMIDAZOL PADA BAKTERI (Staphilococcus aureus) DENGAN PARAMETER ELEKTRONIKMETODE AUSTIN MODEL (AM 1) - Rizqi Nur Azizah; Gemini Alam; Yusnita Rifai; Christiana Lethe (Fakultas Farmasi UMI, 2013)
A quantitative structure activity relationship study on a series of N-alkyl imidazole analogues using combination of various atomic descriptors and molecular descriptors have been investigated. The research was aimed to obtain mathematic equation Quantitative Structure-Activity Relationship of N-alkyl Imidazole analougues as antibacterial agents at bacteria Staphilococcus aureus with electronic parameters used semiempiric Austin Model 1 (AM1) method .Several statistical expressions were developed using stepwise multiple liner regression analysis. The best quantitative structure activity relationship models were further validated by leave-one-out method of cross-validation. The study revealed that the atomic net charges of C2&C3,E-Homo,E-lumo,dipole moment (µ),and Total Energy (ET) contributed positively, and atomic net charges of C1,N1,&N2,Binding Energy (Eb),RMS Gradient (RMS), and Elecrtonic Energy (Ee) contributed negatively. The quantitative structure activity relationship study provides important structural insights in designing of potent antibacterial agents. Several alternative models which have possibility to express the correlation betwen biological activity and electronic parameters, ”The best model” is represented by a linear function of activity versus atomic net charges of C2&C3 and E-Homo,E-lumo,dipole moment (µ),and Total Energy (Ee) is axpressed by:Log(1/C) = 114,614 (±28,461) + 505,362 (±149,739) qC2 + 247,641(±47,025)qC3 + 0,819(±0,379) E-Homo + 93,404 (±25,997)E-Lumo + -24,982(±6,066)µ + -0,002(±0,000).ET The cross validation analisys give minimal value of PRESS = 106,231and SEP = 3,435Key Words : QSAR, antibacterial, n-alkyl imidazole, Cross Validation Methods